Reassessing the Risk of Venous Thromboembolism (VTE) Events in Women - Changhuai He MD; Jie Chu MS; Yiqing Li MD, PhD; Yiping Dang MD, PhD; Kaming Xue MD, PhD; Chuanqi Cai MD, PhD (Clinical and Applied Thrombosis/Hemostasis)
This research aims to reassess women's risk of venous thromboembolism (VTE) events. We conducted an in-depth analysis of the environmental risk factors associated with VTE and their interactions with gender while also exploring the genetic underpinnings of the disease. VTE is identified as a multifactorial condition influenced by a combination of genetic, non-predisposing, and predisposing environmental factors. We further investigated the genetic basis of VTE, focusing on the identification and analysis of risk loci, as well as gene interaction networks and genetic analyses, which offer significant insights into the pathogenesis of VTE. Recognizing the critical role of gender in assessing VTE risk and developing prevention strategies, this research underscores the necessity of adopting an integrated perspective that accounts for individual vulnerabilities at both genetic and environmental levels to formulate effective preventive measures.